Preliminary Result of Seismic Hydrodynamic Pressure on Bridge Pier with Submerged Depth from a Shaking Table Model Test. Issue 1 (March 2020) - Liu, Haiming; Tao, Xiaxin; Tao, Zhengru; Qin, Yifang
Abstract: To deal with the hydrodynamic pressure on bridge pier with submerged depth in water, a shaking table model test is reported in this paper. The model is designed and built for a pier of cable-stayed bridge submerged in 1.5 m water with a scale of 1/50. Two sets of motions, for E1 and E2 levels are input in two bi-directions, transverse and vertical, and longitudinal and vertical. The results show that the hydrodynamic pressure is getting larger with submerged depth obviously, with a. increasing rate larger than that for the formula in our existing design guidelines, but smaller than that by Westergaard.